Staging, playing, pyrotechnics and magic : conventions of performance in early English theatre : shifting paradigms in early English drama studies - Butterworth, Philip; Harrop, Peter (Professor of Drama) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"In this selection of research articles Butterworth focuses on investigation of the practical and technical means by which early English theatre, from the fifteenth to the early seventeenth century, was performed. Matters of staging for both 'pageant vehicle' and 'theatre-in-the-round' are described and analysed to consider their impact on playing by players, expositors, narrators and prompters. All these operators also functioned to promote the closely aligned disciplines of pyrotechnics and magic (legerdemain or sleight of hand) which also influence the nature of the presented theatre. The sixteen chapters form four clearly identified parts-staging, playing, pyrotechnics and magic-and drawing on a wealth of primary source material, Butterworth encourages the reader to rediscover and reappreciate the actors, magicians, wainwrights and wheelwrights, pyrotechnists, and (in modern terms) the special effects people and event managers who brought these early texts to theatrical life on busy city streets and across open arenas. The chapters variously explore and analyse the important backwaters of material culture that enabled, facilitated and shaped performance yet have received scant scholarly attention. It is here, among the itemised payments to carpenters and chemists, the noted requirements of mechanics and wheelwrights, or tucked away among the marginalia of suppliers of staging and ingenious devices that Butterworth has made his stamping ground. This is a fascinating introduction to the very 'nuts and bolts' of early theatre. Staging, Playing, Pyrotechnics and Magic: Conventions of Performance in Early English Theatre is a closely argued celebration of stagecraft that will appeal to academics and students of performance, theatre history and medieval studies as well as history and literature more broadly. It constitutes the eighth volume in the Routledge series Shifting Paradigms in Early English Drama Studies and continues the valuable work of that series (of which Butterworth is a general editor) in bringing significant and expert research articles to a wider audience"--
The York Mercers pageant vehicle, 1433-1467 : wheels, steering, and control -- Hugh Platte's collapsible wagon -- Pageant carriage maintenance at Chester -- Jetties, pentices, purprestures and ordure : obstacles to pageants and processions in London -- The work of William Parnell, supplier of staging and ingenious devices, and his role in the visit of Elizabeth Woodville to Norwich in 1469 / with Michael Spence -- The York crucifixion : actor/audience relationship -- Jean Fouquets The martyrdom of St Apollonia and the rape of the Sabine women as iconographical evidence of medieval theatre practice -- Richard Carews ordinary : the first English director in the narrator, the expositor, and the prompter in European medieval theatre -- Prompting in full view of the audience : the Groningen experiment -- Hellfire : flame as special effect -- The light of heaven : flame as special effect -- The providers of pyrotechnics in plays and celebrations -- Juggling and staging tricks in early theatre -- Brandon, feats and Hocus Pocus : jugglers three -- Hocus Pocus Junior : further confirmation of its author -- Is there any further value to be gained from re-staging medieval theatre?
Keywords: Theater -- England -- History -- 16th century; Theaters -- Stage-setting and scenery -- England -- History; Pageants -- England -- History -- 16th century; Processions -- England -- History -- 16th century; Stage props -- England -- History -- 16th century; Stage machinery -- England -- History -- 16th century; Fireworks in the theater -- England -- History; Tricks -- England -- History; HISTORY / General